High current density electrolytic active cathode and preparation method thereof
By forming the metal oxide cathode bottom layer and outer layer active coating on the conductive substrate, the existing high current density electrolytic active cathode has solved the problem of high hydrogen evolution overpotential and short service life under high current density conditions, and a high current density electrolytic cathode with low energy consumption, long life and stable operation is achieved, meeting the long-term and stable operation needs of chlor-alkali production and reducing costs.
Patent Information
- Application Number
- CN202110984700.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-08-25
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2041-08-25
AI Technical Summary
When the existing high-current density electrolytic active cathode is operated under high current density conditions, the hydrogen evolution overpotential is high, the service life is short, and the energy consumption is large, making it difficult to meet the long-term and stable operation needs of chlor-alkali production users.
The metal oxide cathode bottom active coating and outer active coating are coated with a conductive matrix. The bottom coat is composed of oxides of the transition element Group VIII and oxides of the lanthanides. The outer coat is composed of oxides of the transition element Group VIII, and an efficient active coating is formed through specific process steps.
Operating at a high current density of 8KA/m2, the hydrogen evolution overpotential is low, the service life is long, the energy consumption is lower, and the operation is stable. It meets the long-term high current density driving needs of chlor-alkali production users, while reducing equipment investment costs and improving economic benefits.
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrolysis, and in particular to a high current density electrolysis active cathode and a preparation method thereof. Background Art
[0002] The chlor-alkali industry is an industrialized production industry with chlorine and caustic soda as its main products. Its products are widely used in my country's economic development and play an important role in promoting social and economic development. In recent years, with the rapid development of the chlor-alkali industry and the continuous expansion of the chlor-alkali product market, the technology of ion membrane electrolyzers and their supporting electrodes for chlor-alkali electrolysis equipment has been continuously innovated. In particular, with the improvement of the technical management level of chlor-alkali users, it has become possible for ion membrane electrolyzers to operate normally under high current density conditions. At the same time, users have also put forward higher requirements for the power consumption per ton of alkali and the life of electrodes of ion membrane electrolyzers. The focus has been on developing ion membrane electrolyzer electrodes suitable for high current density operation to meet users' needs to reduce energy consumption in chlor-alkali production and ensure stable operation of equipment under long-term high current density.
[0003] The current density of conventional electrolytic active cathode operation is usually 2KA / m 2 -4KA / m 2 This requires the development of a device that operates at a high current density, that is, 4KA / m 2 The electrolytic active cathode operating at the above current density requires an electrode that can have a low hydrogen evolution overpotential and a long service life at high current density. However, the existing high current density electrolytic active cathode generally does not have such performance. The latest electrolytic active cathode technology is at 6KA / m 2 When running at a current density of about 75mV, the hydrogen evolution overpotential is about 75mV.
[0004] After experimental research, this patent has developed a cathode suitable for high current density electrolysis. Under high current density electrolysis conditions, the electrode has a good life, reduced energy consumption, and significantly improved economic benefits with reduced costs. Summary of the invention
[0005] The present invention aims to provide a kind of 2 The cathode of the ion membrane electrolyzer is an ion membrane electrolyzer that can operate at a high current density. The cathode has a low hydrogen evolution overpotential under high current density electrolysis conditions, a long service life, lower energy consumption, and stable operation. This can meet the needs of chlor-alkali production users for long-term high current density start-up and stable operation, and at the same time help users reduce equipment investment costs and improve economic benefits. The high current density electrolysis active cathode and its preparation method
[0006] The high current density electrolysis active cathode of the present invention comprises a conductive substrate, which is made of a metal material, the outer surface of which is covered with a metal oxide cathode bottom active coating, the outer surface of which is covered with a metal oxide cathode outer layer active coating, the metal oxide cathode bottom active coating is composed of an oxide of a transition element of Group VIII and an oxide of a lanthanide element, and the metal oxide cathode outer layer active coating is composed of an oxide of a transition element of Group VIII;
[0007] The ratio of the number of atoms of transition elements of group VIII to the number of atoms of lanthanide elements in the metal oxide cathode bottom active coating is 2.3-10.1, and the content of oxides of transition elements of group VIII in the metal oxide cathode bottom active coating is 6-16 g / m 2 ;
[0008] The ratio of the number of atoms of transition elements of group VIII in the bottom active coating of the metal oxide cathode to the number of atoms of transition elements of group VIII in the outer active coating of the metal oxide cathode is 5.9-23.4.
[0009] Preferably, the transition element of Group VIII in the metal oxide cathode bottom active coating is ruthenium, rhodium, palladium and / or platinum, and the lanthanide element is cerium and / or praseodymium;
[0010] The transition element of Group VIII in the outer active coating of the metal oxide cathode is ruthenium, rhodium, palladium and / or platinum.
[0011] The surface area of the active cathode conductive substrate nickel wire metal substrate is 12-16cm 2 / g.
[0012] Preferably, the ratio of the number of atoms of ruthenium, rhodium, palladium and / or platinum to the number of atoms of cerium and / or praseodymium in the metal oxide cathode bottom active coating is 4.0-8.1, and the content of ruthenium, rhodium, palladium and / or platinum oxide in the metal oxide cathode bottom active coating is 8-14 g / m 2 ;
[0013] The ratio of the number of atoms of ruthenium, rhodium, palladium and / or platinum in the bottom active coating of the metal oxide cathode to the number of atoms of ruthenium, rhodium, palladium and / or platinum in the outer active coating of the metal oxide cathode is 8.8-17.6.
[0014] The surface area of the active cathode conductive substrate nickel wire metal substrate is 13-15cm 2 / g.
[0015] The method for preparing the high current density electrolytic active cathode of the present invention comprises the following steps:
[0016] A. Clean the conductive substrate made of metal material, remove the surface dirt of the conductive substrate, make the surface of the conductive substrate rough, and thermally oxidize it at 400℃-500℃ for 15-45 minutes;
[0017] B. preparing soluble salts of transition elements of Group VIII and soluble salts of lanthanide elements;
[0018] C. Dissolving a soluble salt of a transition element of group VIII with dilute hydrochloric acid, and adding a soluble salt of a soluble salt of a lanthanide element to obtain a cathode bottom layer active coating liquid, wherein the content of the metal element in the cathode bottom layer active coating liquid is 125 g-175 g / L, and the ratio of the number of atoms of the transition element of group VIII to the number of atoms of the lanthanide element is 2.3-10.1;
[0019] Dissolving a soluble salt of transition element group VIII with dilute nitric acid to obtain a cathode outer layer active coating solution, wherein the content of the metal element in the cathode outer layer active coating solution is 55 g-85 g / L based on the metal component;
[0020] The ratio of the number of atoms of transition elements of group VIII in the cathode bottom layer active coating liquid to the number of atoms of transition elements of group VIII in the cathode outer layer active coating liquid is 5.9-23.4;
[0021] D. Apply the cathode bottom active coating liquid obtained in step C on the conductive substrate treated in step A, heat the conductive substrate to 400°C-550°C in an air atmosphere for 10 minutes to 50 minutes, thereby forming a metal oxide cathode active coating on the surface of the conductive substrate; then apply the cathode bottom active coating liquid obtained in step C on the conductive substrate again, heat the conductive substrate to 400°C-550°C in an air atmosphere for 10 minutes to 50 minutes, and repeat this process several times until the content of the oxide of the transition element Group VIII in the metal oxide cathode bottom active coating is 6-16 g / m 2 ;
[0022] E. Apply the cathode outer layer active coating liquid obtained in step C on the conductive substrate treated in step D, heat the conductive substrate to 400°C-550°C in an air atmosphere for 10 minutes to 50 minutes, thereby forming a metal oxide cathode active coating on the surface of the conductive substrate; then apply the cathode outer layer active coating liquid obtained in step C on the conductive substrate again, heat the conductive substrate to 400°C-550°C in an air atmosphere for 10 minutes to 50 minutes, and repeat this process several times until the ratio of the number of atoms of the transition element of group VIII in the metal oxide cathode outer layer active coating to the number of atoms of the transition element of group VIII in the metal oxide cathode bottom layer active coating reaches the requirement, thereby obtaining a high current density active gas precipitation cathode.
[0023] Preferably, in step C, the content of metal elements in the cathode bottom active coating solution is 130 g / L-170 g / L, wherein the ratio of the number of atoms of transition elements of group VIII to the number of atoms of lanthanide elements is 4.0-8.1;
[0024] According to the metal component, the content of metal elements in the cathode outer layer active coating liquid is 60g / L-80g / L;
[0025] The transition element of Group VIII in the active coating of the metal oxide cathode bottom layer is ruthenium, rhodium, palladium and / or platinum, and the lanthanide element is cerium and / or praseodymium;
[0026] The transition element of Group VIII in the outer active coating of the metal oxide cathode is ruthenium, rhodium, palladium and / or platinum;
[0027] In the step D, the conductive substrate is heated to 420° C.-520° C. in an air atmosphere for 15 minutes-45 minutes, thereby forming a metal oxide cathode active coating on the surface of the conductive substrate; then the cathode bottom active coating liquid obtained in step C is applied to the conductive substrate again, and the conductive substrate is heated to 420° C.-520° C. in an air atmosphere for 15 minutes-45 minutes, and this is repeated 6-12 times until the content of the oxide of the transition element group VIII in the metal oxide cathode bottom active coating is 8-14 g / m 2 ;
[0028] In the step E, the conductive substrate is heated to 420° C.-520° C. in an air atmosphere for 15 minutes-45 minutes, thereby forming a metal oxide cathode active coating on the surface of the conductive substrate; then the cathode outer layer active coating liquid obtained in step C is coated on the conductive substrate again, and the conductive substrate is heated to 420° C.-520° C. in an air atmosphere for 15 minutes-45 minutes, and this is repeated several times until the ratio of the number of atoms of the transition element of group VIII in the metal oxide cathode outer layer active coating to the number of atoms of the transition element of group VIII in the metal oxide cathode bottom layer active coating reaches the requirement, thereby obtaining a high current density active gas precipitation cathode.
[0029] The high current density electrolytic active cathode and the preparation method thereof adopt the unique process steps of the present invention, including that the active cathode bottom layer coating and the outer layer coating are made of two different solution systems, the bottom layer coating liquid is a hydrochloric acid solution, the outer layer coating liquid is a nitric acid solution, and the ratio of the number of atoms of the transition element group VIII to the number of atoms of the lanthanide element in the metal oxide cathode bottom layer active coating is 2.3-10.1, and the content of the oxide of the transition element group VIII in the metal oxide cathode bottom layer active coating is 6-16 g / m 2 , the ratio of the number of atoms of transition elements of group VIII in the bottom active coating of the metal oxide cathode to the number of atoms of transition elements of group VIII in the outer active coating of the metal oxide cathode is 5.9-23.4; because the active cathode hydrogen evolution active points of the high current density electrolysis active cathode of the present invention are increased, the electrode life is long during high current density electrolysis, the electrolysis energy consumption is low, and the electrode manufacturing process is excellent and the cost performance is improved. Therefore, the high current density electrolysis active cathode of the present invention and its preparation method have the advantages of being able to produce high current density electrolysis at 8KA / m 2 The cathode of the ion membrane electrolyzer is operated under high current density. The oxygen evolution overpotential is low under high current density electrolysis conditions, the service life is long, the energy consumption is lower, and the operation is stable. It can meet the needs of chlor-alkali production users for long-term high current density start-up and stable operation, and at the same time help users reduce equipment investment costs and improve economic benefits.
[0030] Other details and features of the high current density electrolytic active cathode and its preparation method of the present invention will become clear by reading the embodiments described in detail below. DETAILED DESCRIPTION
[0031] The high current density electrolysis active cathode of the present invention comprises a conductive substrate, which is made of a metal material, the outer surface of which is covered with a metal oxide cathode bottom active coating, the outer surface of which is covered with a metal oxide cathode outer layer active coating, the metal oxide cathode bottom active coating is composed of an oxide of a transition element of Group VIII and an oxide of a lanthanide element, and the metal oxide cathode outer layer active coating is composed of an oxide of a transition element of Group VIII;
[0032] The ratio of the number of atoms of transition elements of group VIII to the number of atoms of lanthanide elements in the metal oxide cathode bottom active coating is 2.3-10.1, and the content of oxides of transition elements of group VIII in the metal oxide cathode bottom active coating is 6-16 g / m 2 ;
[0033] The ratio of the number of atoms of transition elements of group VIII in the bottom active coating of the metal oxide cathode to the number of atoms of transition elements of group VIII in the outer active coating of the metal oxide cathode is 5.9-23.4.
[0034] The surface area of the active cathode conductive substrate nickel wire metal substrate is 12-16 cm2 / g.
[0035] As a further improvement of the present invention, the transition element of Group VIII in the above-mentioned metal oxide cathode bottom active coating is ruthenium, rhodium, palladium and / or platinum, and the lanthanide element is cerium and / or praseodymium;
[0036] The transition element of Group VIII in the outer active coating of the metal oxide cathode is ruthenium, rhodium, palladium and / or platinum.
[0037] The ratio of the number of atoms of transition elements of group VIII to the number of atoms of lanthanide elements in the metal oxide cathode bottom active coating is 2.3-10.1, and the content of oxides of transition elements of group VIII in the metal oxide cathode bottom active coating is 6-16 g / m2;
[0038] The ratio of the number of atoms of transition elements of group VIII in the bottom active coating of the metal oxide cathode to the number of atoms of transition elements of group VIII in the outer active coating of the metal oxide cathode is 5.9-23.4.
[0039] Preferably, the transition element of Group VIII in the metal oxide cathode bottom active coating is ruthenium, rhodium, palladium and / or platinum, and the lanthanide element is cerium and / or praseodymium;
[0040] The transition element of Group VIII in the outer active coating of the metal oxide cathode is ruthenium, rhodium, palladium and / or platinum.
[0041] Preferably, the ratio of the number of atoms of ruthenium, rhodium, palladium and / or platinum to the number of atoms of cerium and / or praseodymium in the metal oxide cathode bottom active coating is 4.0-8.1, and the content of ruthenium, rhodium, palladium and / or platinum oxide in the metal oxide cathode bottom active coating is 8-14 g / m 2 ;
[0042] The ratio of the number of atoms of ruthenium, rhodium, palladium and / or platinum in the bottom active coating of the metal oxide cathode to the number of atoms of ruthenium, rhodium, palladium and / or platinum in the outer active coating of the metal oxide cathode is 8.8-17.6.
[0043] The surface area of the active cathode conductive substrate nickel wire metal substrate is 13-15cm 2 / g.
[0044] The method for preparing the high current density electrolytic active cathode of the present invention comprises the following steps:
[0045] A. Clean the conductive substrate made of metal material, remove the surface dirt of the conductive substrate, make the surface of the conductive substrate rough, and thermally oxidize it at 400℃-500℃ for 15-45 minutes;
[0046] B. preparing soluble salts of transition elements of Group VIII and soluble salts of lanthanide elements;
[0047] C. Dissolving a soluble salt of a transition element of group VIII with dilute hydrochloric acid, and adding a soluble salt of a soluble salt of a lanthanide element to obtain a cathode bottom layer active coating liquid, wherein the content of the metal element in the cathode bottom layer active coating liquid is 125 g-175 g / L, and the ratio of the number of atoms of the transition element of group VIII to the number of atoms of the lanthanide element is 2.3-10.1;
[0048] Dissolving a soluble salt of the transition element group VIII with dilute nitric acid to obtain a cathode outer layer active coating solution, wherein the content of the metal element in the cathode outer layer active coating solution is 55 g / L-85 g / L based on the metal component;
[0049] The ratio of the number of atoms of transition elements of group VIII in the cathode bottom layer active coating liquid to the number of atoms of transition elements of group VIII in the cathode outer layer active coating liquid is 5.9-23.4;
[0050] D. Apply the cathode bottom active coating liquid obtained in step C on the conductive substrate treated in step A, heat the conductive substrate to 400°C-550°C in an air atmosphere for 10 minutes to 50 minutes, thereby forming a metal oxide cathode active coating on the surface of the conductive substrate; then apply the cathode bottom active coating liquid obtained in step C on the conductive substrate again, heat the conductive substrate to 400°C-550°C in an air atmosphere for 10 minutes to 50 minutes, and repeat this process several times until the content of the oxide of the transition element Group VIII in the metal oxide cathode bottom active coating is 6-16 g / m 2 ;
[0051] E. Apply the cathode outer layer active coating liquid obtained in step C on the conductive substrate treated in step D, heat the conductive substrate to 400°C-550°C in an air atmosphere for 10 minutes to 50 minutes, thereby forming a metal oxide cathode active coating on the surface of the conductive substrate; then apply the cathode outer layer active coating liquid obtained in step C on the conductive substrate again, heat the conductive substrate to 400°C-550°C in an air atmosphere for 10 minutes to 50 minutes, and repeat this process several times until the ratio of the number of atoms of the transition element of group VIII in the metal oxide cathode outer layer active coating to the number of atoms of the transition element of group VIII in the metal oxide cathode bottom layer active coating reaches the requirement, thereby obtaining a high current density active gas precipitation cathode.
[0052] As a further improvement of the present invention, in the above step C, the content of metal elements in the cathode bottom active coating solution is 130g-170g / L, wherein the ratio of the number of atoms of transition elements of group VIII to the number of atoms of lanthanide elements is 4.1-8.0;
[0053] According to the metal composition, the content of metal elements in the cathode outer layer active coating liquid is 60g-80g / L;
[0054] The ratio of the number of atoms of transition elements of group VIII in the cathode bottom layer active coating liquid to the number of atoms of transition elements of group VIII in the cathode outer layer active coating liquid is 8.8-17.6;
[0055] The transition elements of Group VIII in the active coating layer of the metal oxide cathode bottom layer are ruthenium, rhodium, palladium and / or platinum, and the lanthanide elements are cerium and / or praseodymium;
[0056] The transition element of Group VIII in the outer active coating of the metal oxide cathode is ruthenium, rhodium, palladium and / or platinum;
[0057] In the step D, the conductive substrate is heated to 420° C.-520° C. in an air atmosphere for 15 minutes-45 minutes, thereby forming a metal oxide cathode active coating on the surface of the conductive substrate; then the cathode bottom active coating liquid obtained in step C is applied to the conductive substrate again, and the conductive substrate is heated to 420° C.-520° C. in an air atmosphere for 15 minutes-45 minutes, and this is repeated 6-12 times until the content of the oxide of the transition element group VIII in the metal oxide cathode bottom active coating is 8-14 g / m 2 ;
[0058] In the step E, the conductive substrate is heated to 420° C.-520° C. in an air atmosphere for 15 minutes-45 minutes, thereby forming a metal oxide cathode active coating on the surface of the conductive substrate; then the cathode outer layer active coating liquid obtained in step C is coated on the conductive substrate again, and the conductive substrate is heated to 420° C.-520° C. in an air atmosphere for 15 minutes-45 minutes, and this is repeated 1-4 times until the ratio of the number of atoms of the transition element of group VIII in the metal oxide cathode outer layer active coating to the number of atoms of the transition element of group VIII in the metal oxide cathode bottom layer active coating meets the requirement, thereby obtaining a high current density active gas precipitation cathode.
[0059] The mass percentage of each element in the above active coating calculated as metal components can be obtained by detecting with an X-ray fluorescence tester.
[0060] The cathode for high current density electrolysis of the present invention and the preparation method thereof adopt the unique process steps of the present invention, including that the active cathode bottom layer coating and the outer layer coating are made by using two different solution systems, the bottom layer coating liquid is a hydrochloric acid solution, and the outer layer coating liquid is a nitric acid solution; due to the use of the above-mentioned unique technical features, the cathode for high current density electrolysis of the present invention can operate stably for a long time under electrolysis conditions with relatively high current density, and at the same time has a relatively low hydrogen evolution overpotential, thus meeting the energy-saving, consumption-reducing, quality-improving and efficiency-enhancing use requirements of chlor-alkali users; in addition, the catalyst coating adopted by the cathode of the present invention and the preparation method thereof have lower costs, thus being able to reduce the cost and investment of chlor-alkali electrolysis equipment.
[0061] Example 1
[0062] The method for preparing the high current density electrolytic active cathode of the present invention is as follows:
[0063] 1. Dissolve the soluble salts of ruthenium, cerium and platinum with hydrochloric acid, and prepare a cathode bottom active coating liquid with a total precious metal content of 150 g / L according to the atomic weight ratio of ruthenium 70: cerium 20: platinum 10 for the preparation of the bottom coating, and prepare a nitric acid solution of platinum into a cathode outer active coating liquid with a metal content of 55 g / L for the preparation of the outer coating.
[0064] 2. Select The nickel wire mesh is woven as a conductive matrix, so that the surface area of the conductive matrix reaches 17cm 2 The nickel substrate was cleaned and surface roughened, and then thermally oxidized at 500°C for 40 minutes.
[0065] 3. The cathode bottom active coating liquid obtained in step 1 is coated on the metal nickel wire mesh obtained in step 2, and then dried at 80°C for 3 minutes, and then thermally oxidized at 565°C for 30 minutes; the above process is repeated 12 times to complete the bottom coating preparation.
[0066] 4. The cathode outer layer active coating liquid obtained in step 1 is coated on the metal nickel wire mesh coated with the base layer coating obtained in step 3, and then thermally oxidized at 500°C for 15 minutes; the above process is repeated 4 times to complete the outer layer coating preparation.
[0067] 5. The metal nickel wire mesh coated with the outer coating obtained in step 4 was thermally oxidized at 585° C. for 100 minutes to obtain electrode A1 in which the ratio of the number of metal atoms in the bottom coating to that in the outer coating was 17:1.
[0068] Example 2
[0069] The method for preparing the high current density electrolytic active cathode of the present invention is as follows:
[0070] 1. Dissolve the soluble salts of ruthenium and cerium with hydrochloric acid, and prepare a cathode bottom active coating liquid with a total precious metal content of 135 g / L according to the atomic weight ratio of ruthenium 70:cerium 30 for the preparation of the bottom coating, and prepare a nitric acid solution of platinum into a cathode outer active coating liquid with a metal content of 85 g / L for the preparation of the outer coating.
[0071] 2. Select The nickel wire mesh is woven as a conductive matrix, so that the surface area of the conductive matrix reaches 13cm 2 The metal nickel substrate was cleaned and surface roughened, and then thermally oxidized at 400°C for 15 minutes.
[0072] 3. The cathode bottom active coating liquid obtained in step 1 is applied to the metal nickel wire mesh obtained in step 2, and then dried at 160°C for 15 minutes, and then thermally oxidized at 500°C for 45 minutes; the above process is repeated 8 times to complete the bottom coating preparation.
[0073] 4. The cathode outer layer active coating liquid obtained in step 1 is coated on the metal nickel wire mesh coated with the base layer obtained in step 3, and then thermally oxidized at 500°C for 40 minutes; the above process is repeated twice to complete the outer layer coating.
[0074] 5. The metal nickel wire mesh coated with the outer coating obtained in step 4 was thermally oxidized at 550° C. for 100 minutes to obtain electrode A2 in which the ratio of the number of metal atoms in the bottom coating to that in the outer coating was 8:1.
[0075] Example 3
[0076] The method for preparing the high current density electrolytic active cathode of the present invention is as follows:
[0077] 1. Dissolve the soluble salts of ruthenium, cerium and platinum with hydrochloric acid, and prepare a cathode bottom layer active coating liquid with a total precious metal content of 140 g / L according to the atomic weight ratio of ruthenium 80: cerium 10: platinum 10 for the preparation of the bottom layer coating, and prepare a nitric acid solution of platinum into a cathode outer layer active coating liquid with a metal content of 70 g / L for the preparation of the outer layer coating.
[0078] 2. Select Nickel wire mesh is woven as a conductive matrix, so that the surface area of the conductive matrix reaches 15cm 2 The nickel substrate was cleaned and surface roughened, and then thermally oxidized at 450°C for 30 minutes.
[0079] 3. The cathode bottom active coating liquid obtained in step 1 is applied onto the metal nickel wire mesh obtained in step 2, and then dried at 160°C for 10 minutes, and then thermally oxidized at 530°C for 25 minutes; the above process is repeated 10 times to complete the bottom coating preparation.
[0080] 4. The cathode outer layer active coating liquid obtained in step 1 is coated on the metal nickel wire mesh coated with the base layer obtained in step 3, and then thermally oxidized at 530°C for 25 minutes; the above process is repeated 3 times to complete the outer layer coating.
[0081] 5. The metal nickel wire mesh coated with the outer coating obtained in step 4 was thermally oxidized at 530° C. for 80 minutes to obtain an electrode A3 in which the ratio of the number of metal atoms in the bottom coating to that in the outer coating was 10:1.
[0082] Example 4
[0083] The method for preparing the high current density electrolytic active cathode of the present invention is as follows:
[0084] 1. Dissolve the soluble salts of ruthenium, cerium and platinum with hydrochloric acid, and prepare a cathode bottom active coating liquid with a total precious metal content of 140 g / L according to the atomic weight ratio of ruthenium 85: cerium 10: platinum 5 for the preparation of the bottom coating, and prepare a nitric acid solution of platinum into a cathode outer active coating liquid with a metal content of 75 g / L for the preparation of the outer coating.
[0085] 2. Select The nickel wire mesh is woven as a conductive matrix, so that the surface area of the conductive matrix reaches 14cm 2The nickel substrate was cleaned and surface roughened, and then thermally oxidized at 450°C for 30 minutes.
[0086] 3. The cathode bottom active coating liquid obtained in step 1 is applied onto the metal nickel wire mesh obtained in step 2, and then dried at 100°C for 10 minutes, and then thermally oxidized at 510°C for 30 minutes; the above process is repeated 9 times to complete the bottom coating preparation.
[0087] 4. The cathode outer layer active coating liquid obtained in step 1 is coated on the metal nickel wire mesh coated with the base layer obtained in step 3, and then thermally oxidized at 510°C for 20 minutes; the above process is repeated 3 times to complete the outer layer coating.
[0088] 5. The metal nickel wire mesh coated with the outer coating obtained in step 4 was thermally oxidized at 510° C. for 80 minutes to obtain electrode A4 in which the ratio of the number of metal atoms in the bottom coating to that in the outer coating was 9:1.
[0089] Example 5
[0090] The method for preparing the high current density electrolytic active cathode of the present invention is as follows:
[0091] 1. Dissolve the soluble salts of ruthenium, cerium and platinum with hydrochloric acid, and prepare a cathode bottom layer active coating liquid with a total precious metal content of 140 g / L according to the atomic weight ratio of ruthenium 80: cerium 15: platinum 5 for the preparation of the bottom layer coating, and prepare a nitric acid solution of platinum into a cathode outer layer active coating liquid with a metal content of 75 g / L for the preparation of the outer layer coating.
[0092] 2. Select The nickel wire mesh is woven as a conductive matrix, so that the surface area of the conductive matrix reaches 14cm 2 The nickel substrate was cleaned and surface roughened, and then thermally oxidized at 450°C for 30 minutes.
[0093] 3. The cathode bottom active coating liquid obtained in step 1 is applied onto the metal nickel wire mesh obtained in step 2, and then dried at 130°C for 10 minutes, and then thermally oxidized at 530°C for 30 minutes; the above process is repeated 12 times to complete the bottom coating preparation.
[0094] 4. The cathode outer layer active coating liquid obtained in step 1 is coated on the metal nickel wire mesh coated with the base layer obtained in step 3, and then thermally oxidized at 510°C for 15 minutes; the above process is repeated twice to complete the outer layer coating.
[0095] 5. The metal nickel wire mesh coated with the outer coating obtained in step 4 was thermally oxidized at 530° C. for 80 minutes to obtain electrode A5 in which the ratio of the number of metal atoms in the bottom coating to that in the outer coating was 16:1.
[0096] Example 6
[0097] The method for preparing the high current density electrolytic active cathode of the present invention is as follows:
[0098] 1. Dissolve the soluble salts of ruthenium, cerium and platinum with hydrochloric acid, and prepare a cathode bottom layer active coating liquid with a total precious metal content of 140 g / L according to the atomic weight ratio of ruthenium 80: cerium 15: platinum 5 for the preparation of the bottom layer coating, and prepare a nitric acid solution of platinum into a cathode outer layer active coating liquid with a metal content of 75 g / L for the preparation of the outer layer coating.
[0099] 2. Select The nickel wire mesh is woven as a conductive matrix, so that the surface area of the conductive matrix reaches 14cm 2 The nickel substrate was cleaned and surface roughened, and then thermally oxidized at 450°C for 30 minutes.
[0100] 3. The cathode bottom active coating liquid obtained in step 1 is applied onto the metal nickel wire mesh obtained in step 2, and then dried at 130°C for 10 minutes, and then thermally oxidized at 530°C for 30 minutes; the above process is repeated 10 times to complete the bottom coating preparation.
[0101] 4. The cathode outer layer active coating liquid obtained in step 1 is coated on the metal nickel wire mesh coated with the base layer obtained in step 3, and then thermally oxidized at 510°C for 15 minutes; the above process is repeated 3 times to complete the outer layer coating.
[0102] 5. The metal nickel wire mesh coated with the outer coating obtained in step 4 was thermally oxidized at 530° C. for 80 minutes to obtain electrode A6 in which the ratio of the number of metal atoms in the bottom coating to that in the outer coating was 10:1.
[0103] Comparative Example 1
[0104] The method for preparing the high current density electrolytic active cathode of the present invention is as follows:
[0105] 1. Dissolve the soluble salts of ruthenium, cerium and platinum with hydrochloric acid, and prepare a cathode bottom layer active coating liquid with a total precious metal content of 140 g / L according to the atomic weight ratio of ruthenium 80: cerium 15: platinum 5 for the preparation of the bottom layer coating, and prepare a nitric acid solution of platinum into a cathode outer layer active coating liquid with a metal content of 75 g / L for the preparation of the outer layer coating.
[0106] 2. Select The nickel wire mesh was woven as a conductive substrate, so that the surface area of the conductive substrate reached 11.5 cm2 / g. The metal nickel substrate was cleaned and surface roughened, and thermally oxidized at 450°C for 30 minutes.
[0107] 3. The cathode bottom active coating liquid obtained in step 1 is applied onto the metal nickel wire mesh obtained in step 2, and then dried at 130°C for 10 minutes, and then thermally oxidized at 530°C for 30 minutes; the above process is repeated 10 times to complete the bottom coating preparation.
[0108] 4. The cathode outer layer active coating liquid obtained in step 1 is coated on the metal nickel wire mesh coated with the base layer obtained in step 3, and then thermally oxidized at 510°C for 15 minutes; the above process is repeated 3 times to complete the outer layer coating.
[0109] 5. The metal nickel wire mesh coated with the outer layer coating obtained in step 4 was thermally oxidized at 530° C. for 80 minutes to obtain an electrode C1 in which the ratio of the number of metal atoms in the bottom coating to that in the outer coating was 10:1.
[0110] Comparative Example 2
[0111] The method for preparing the high current density electrolytic active cathode of the present invention is as follows:
[0112] 1. Dissolve the soluble salts of ruthenium, cerium and platinum with hydrochloric acid, and prepare a cathode bottom layer active coating liquid with a total precious metal content of 140 g / L according to the atomic weight ratio of ruthenium 80: cerium 15: platinum 5 for the preparation of the bottom layer coating, and prepare a nitric acid solution of platinum into a cathode outer layer active coating liquid with a metal content of 75 g / L for the preparation of the outer layer coating.
[0113] 2. Select The nickel wire mesh was woven as a conductive substrate, so that the surface area of the conductive substrate reached 16.5 cm2 / g. The metal nickel substrate was cleaned and surface roughened, and thermally oxidized at 450°C for 30 minutes.
[0114] 3. The cathode bottom active coating liquid obtained in step 1 is applied onto the metal nickel wire mesh obtained in step 2, and then dried at 130°C for 10 minutes, and then thermally oxidized at 530°C for 30 minutes; the above process is repeated 10 times to complete the bottom coating preparation.
[0115] 4. The cathode outer layer active coating liquid obtained in step 1 is coated on the metal nickel wire mesh coated with the base layer obtained in step 3, and then thermally oxidized at 510°C for 15 minutes; the above process is repeated 3 times to complete the outer layer coating.
[0116] 5. The metal nickel wire mesh coated with the outer coating obtained in step 4 was thermally oxidized at 530° C. for 80 minutes to obtain an electrode C2 in which the ratio of the number of metal atoms in the bottom coating to that in the outer coating was 10:1.
[0117] Comparative Example 3
[0118] The method for preparing the high current density electrolytic active cathode of the present invention is as follows:
[0119] 1. Dissolve the soluble salts of ruthenium, cerium and platinum with hydrochloric acid, and prepare a cathode bottom layer active coating liquid with a total precious metal content of 140 g / L according to the atomic weight ratio of ruthenium 80: cerium 15: platinum 5 for the preparation of the bottom layer coating, and prepare a platinum hydrochloric acid solution into a cathode outer layer active coating liquid with a metal content of 75 g / L for the preparation of the outer layer coating.
[0120] 2. Select The nickel wire mesh is woven as a conductive substrate, so that the surface area of the conductive substrate reaches 14 cm2 / g. The metal nickel substrate is cleaned and surface roughened, and thermally oxidized at 450°C for 30 minutes.
[0121] 3. The cathode bottom active coating liquid obtained in step 1 is applied onto the metal nickel wire mesh obtained in step 2, and then dried at 130°C for 10 minutes, and then thermally oxidized at 530°C for 30 minutes; the above process is repeated 10 times to complete the bottom coating preparation.
[0122] 4. The cathode outer layer active coating liquid obtained in step 1 is coated on the metal nickel wire mesh coated with the base layer obtained in step 3, and then thermally oxidized at 510°C for 15 minutes; the above process is repeated 3 times to complete the outer layer coating.
[0123] 5. The metal nickel wire mesh coated with the outer coating obtained in step 4 was thermally oxidized at 530° C. for 80 minutes to obtain an electrode C3 in which the ratio of the number of metal atoms in the bottom coating to that in the outer coating was 10:1.
[0124] Comparative Example 4
[0125] The method for preparing the high current density electrolytic active cathode of the present invention is as follows:
[0126] 1. Dissolve the soluble salts of ruthenium, cerium and platinum in nitric acid, and prepare a cathode bottom active coating liquid with a total precious metal content of 140 g / L according to the atomic weight ratio of ruthenium 80: cerium 15: platinum 5 for the preparation of the bottom coating, and prepare a nitric acid solution of platinum into a cathode outer active coating liquid with a metal content of 75 g / L for the preparation of the outer coating.
[0127] 2. Select The nickel wire mesh is woven as a conductive substrate, so that the surface area of the conductive substrate reaches 14 cm2 / g. The metal nickel substrate is cleaned and surface roughened, and thermally oxidized at 450°C for 30 minutes.
[0128] 3. The cathode bottom active coating liquid obtained in step 1 is applied onto the metal nickel wire mesh obtained in step 2, and then dried at 130°C for 10 minutes, and then thermally oxidized at 530°C for 30 minutes; the above process is repeated 10 times to complete the bottom coating preparation.
[0129] 4. The cathode outer layer active coating liquid obtained in step 1 is coated on the metal nickel wire mesh coated with the base layer obtained in step 3, and then thermally oxidized at 510°C for 15 minutes; the above process is repeated 3 times to complete the outer layer coating.
[0130] 5. The metal nickel wire mesh coated with the outer coating obtained in step 4 was thermally oxidized at 530° C. for 80 minutes to obtain an electrode C4 in which the ratio of the number of metal atoms in the bottom coating to that in the outer coating was 10:1.
[0131] Example 7
[0132] All high current density electrolytic active cathodes of the present invention were tested by the following method: 8KA / m 2 Electrolysis was continued for 14 days at a current density of 6kA / m. The cathode weight loss before and after electrolysis was calculated using a balance. The residual percentage of the cathode coating before and after electrolysis was calculated using an X-ray fluorescence spectrometer. The specific testing equipment tested the cathode after continuous electrolysis at 6kA / m 2 Hydrogen evolution overpotential. The test results are shown in the following table:
[0133] Table 1.
[0134] Serial number Electrode No. Lifetime weight loss mg Coating residue% <![CDATA[8KA / m 2 Hydrogen evolution overpotential mV]]> 1 A1 2.4 96.2 80 2 A2 3.3 93.1 67 3 A3 1.0 97.0 74 4 A4 0.9 95.3 71 5 A5 0.3 97.6 69 6 A6 0.3 99.8 70 7 C1 6.8 94.1 99 8 C2 5.3 94.7 108 9 C3 8.3 89.7 102 10 C4 7.2 91.2 97
[0135] The data listed in Table 1 show that the high current density electrolytic active cathode of the present invention optimizes the composition and ratio of the bottom active coating so that the bonding force with the substrate required by the present invention is enhanced, the weight loss after electrolysis is very small, and the coating residue is improved; at the same time, the active coating of the present invention is coated on the surface area of the substrate in accordance with the actual operation of the electrode and the comprehensive operation effect, and the specific surface area is maximized, and the electrode active coating is miniaturized, so that the electrode is more conducive to contact with the electrolyte and the gas escapes quickly from the electrode surface when the overall difference in active ingredients is not large, thereby ensuring that the electrode has a lower hydrogen evolution overpotential and less energy consumption under high current density; in addition, the present invention adopts a double coating method of a bottom active coating and an outer active coating, which can reduce the amount of precious metals and reduce the cost of the electrode on the one hand, and on the other hand, it is unexpectedly found during the test process of the present invention that although the bottom active coating is prepared by hydrochloric acid solution, the outer active coating is prepared by nitric acid solution. Solution preparation, but by screening and optimizing the components of the electrode active coating, the overall performance of the electrode is better than the performance of the electrode prepared by using hydrochloric acid solution or nitric acid solution for both the bottom layer and the outer layer, and the electrode life weight loss, coating residue and hydrogen evolution overpotential are significantly improved, which is different from traditional cognition. The reason is that the active coating prepared by the bottom layer of the present invention using hydrochloric acid solution itself is better combined with the substrate, and the nitric acid solution used in the outer layer reduces the dissolution of the existing coating, diversifies the morphology of the active components, and enhances the binding force between the outer layer and the inner layer. At the same time, the interaction between similar components in the two active coatings also further improves the binding force between the electrode coatings, so that the electrode coating has more hydrogen evolution active components to ensure the service life and catalytic activity of the electrode under high current density electrolysis conditions. At the same time, the use of the high current density electrolysis active cathode of the present invention can significantly reduce production costs and improve economic benefits. Therefore, the high current density electrolysis active cathode of the present invention can have a longer life, lower energy consumption, and stable operation of the ion membrane electrolyzer cathode under current density electrolysis conditions, so as to meet the long-term high current density start-up and stable operation of chlor-alkali production users, and at the same time help users reduce equipment investment costs and improve economic benefits.
[0136] The above-mentioned embodiments are merely descriptions of the preferred implementation modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary engineering and technical personnel in the field shall fall within the protection scope determined by the claims of the present invention.
Claims
1. High current density electrolytic active cathode, characterized in that: The conductive substrate comprises a conductive substrate made of a metal material, the outer surface of the conductive substrate is coated with a metal oxide cathode bottom active coating, the outer surface of the metal oxide cathode bottom active coating is coated with a metal oxide cathode outer layer active coating, the metal oxide cathode bottom active coating is composed of an oxide of a transition element of Group VIII and an oxide of a lanthanide element, and the metal oxide cathode outer layer active coating is composed of an oxide of a transition element of Group VIII; The ratio of the number of atoms of transition elements of group VIII to the number of atoms of lanthanide elements in the metal oxide cathode bottom active coating is 2.3-10.1, and the content of oxides of transition elements of group VIII in the metal oxide cathode bottom active coating is 6-16 g / m 2 ; The ratio of the number of atoms of the transition element group VIII in the bottom active coating of the metal oxide cathode to the number of atoms of the transition element group VIII in the outer active coating of the metal oxide cathode is 5.9-23.4; The transition element of Group VIII in the active coating of the metal oxide cathode bottom layer is ruthenium, rhodium, palladium and / or platinum, and the lanthanide element is cerium and / or praseodymium; The transition element of Group VIII in the outer active coating of the metal oxide cathode is ruthenium, rhodium, palladium and / or platinum.
2. The high current density electrolysis active cathode according to claim 1, characterized in that: The ratio of the number of atoms of ruthenium, rhodium, palladium and / or platinum to the number of atoms of cerium and / or praseodymium in the metal oxide cathode bottom active coating is 2.9-9.5, and the content of ruthenium, rhodium, palladium and / or platinum oxide in the metal oxide cathode bottom active coating is 6.7-15.3 g / m 2 ; The ratio of the number of atoms of ruthenium, rhodium, palladium and / or platinum in the bottom active coating of the metal oxide cathode to the number of atoms of ruthenium, rhodium, palladium and / or platinum in the outer active coating of the metal oxide cathode is 6.9-21.
4.
3. The high current density electrolysis active cathode according to claim 2, characterized in that: The ratio of the number of atoms of ruthenium, rhodium, palladium and / or platinum to the number of atoms of cerium and / or praseodymium in the metal oxide cathode bottom active coating is 3.5-8.9, and the content of ruthenium, rhodium, palladium and / or platinum oxide in the metal oxide cathode bottom active coating is 7.4-14.7 g / m 2 ; The ratio of the number of atoms of ruthenium, rhodium, palladium and / or platinum in the bottom active coating of the metal oxide cathode to the number of atoms of ruthenium, rhodium, palladium and / or platinum in the outer active coating of the metal oxide cathode is 7.8-19.
5.
4. The high current density electrolysis active cathode according to claim 3, characterized in that: The ratio of the number of atoms of ruthenium, rhodium, palladium and / or platinum to the number of atoms of cerium and / or praseodymium in the metal oxide cathode bottom active coating is 4.0-8.1, and the content of ruthenium, rhodium, palladium and / or platinum oxide in the metal oxide cathode bottom active coating is 8-14 g / m 2 ; The ratio of the number of atoms of ruthenium, rhodium, palladium and / or platinum in the bottom active coating of the metal oxide cathode to the number of atoms of ruthenium, rhodium, palladium and / or platinum in the outer active coating of the metal oxide cathode is 8.8-17.
6.
5. A method for preparing a high current density electrolytic active cathode, characterized in that: It includes the following steps: A. Clean the conductive substrate made of metal material, remove the surface dirt of the conductive substrate, make the surface of the conductive substrate rough, and thermally oxidize it at 400℃-500℃ for 15-45 minutes; B. preparing soluble salts of transition elements of Group VIII and soluble salts of lanthanide elements; C. Dissolving a soluble salt of the transition element group VIII with dilute hydrochloric acid, and adding a soluble salt of a soluble salt of a lanthanide element to obtain a cathode bottom layer active coating liquid, wherein the content of the metal element in the cathode bottom layer active coating liquid is 125 g-175 g / L, and the ratio of the number of atoms of the transition element group VIII to the number of atoms of the lanthanide element is 2.3-10.1; Dissolving a soluble salt of the transition element group VIII with dilute nitric acid to obtain a cathode outer layer active coating solution, wherein the content of the metal element in the cathode outer layer active coating solution is 55 g / L-85 g / L based on the metal component; D. Apply the cathode bottom active coating liquid obtained in step C on the conductive substrate treated in step A, heat the conductive substrate to 400°C-550°C in an air atmosphere for 10 minutes to 50 minutes, thereby forming a metal oxide cathode active coating on the surface of the conductive substrate; then apply the cathode bottom active coating liquid obtained in step C on the conductive substrate again, heat the conductive substrate to 400°C-550°C in an air atmosphere for 10 minutes to 50 minutes, and repeat this process several times until the content of the oxide of the transition element Group VIII in the metal oxide cathode bottom active coating is 6-16 g / m 2 ; E. Applying the cathode outer layer active coating liquid obtained in step C on the conductive substrate treated in step D, heating the conductive substrate to 400° C.-550° C. in an air atmosphere for 10 minutes-50 minutes, thereby forming a metal oxide cathode active coating on the surface of the conductive substrate; then applying the cathode outer layer active coating liquid obtained in step C on the conductive substrate again, heating the conductive substrate to 400° C.-550° C. in an air atmosphere for 10 minutes-50 minutes, and repeating this process for multiple times until the ratio of the number of atoms of the transition element of group VIII in the metal oxide cathode outer layer active coating to the number of atoms of the transition element of group VIII in the metal oxide cathode bottom layer active coating reaches the requirement, that is, the ratio of the number of atoms of the transition element of group VIII in the metal oxide cathode bottom layer active coating to the number of atoms of the transition element of group VIII in the metal oxide cathode outer layer active coating is 5.9-23.4, thereby obtaining a high current density active gas precipitation cathode.
6. The method for preparing a high current density electrolytic active cathode according to claim 5, characterized in that: In the step C, the content of metal elements in the cathode bottom active coating solution is 130 g / L-170 g / L, wherein the ratio of the number of atoms of the transition element group VIII to the number of atoms of the lanthanide elements is 2.9-9.5; According to the metal component, the content of metal elements in the cathode outer layer active coating liquid is 60g / L-80g / L; The transition element of Group VIII in the active coating of the metal oxide cathode bottom layer is ruthenium, rhodium, palladium and / or platinum, and the lanthanide element is cerium and / or praseodymium; The transition element of Group VIII in the outer active coating of the metal oxide cathode is ruthenium, rhodium, palladium and / or platinum; In the step D, the conductive substrate is heated to 420° C.-520° C. in an air atmosphere for 15 minutes-45 minutes, thereby forming a metal oxide cathode active coating on the surface of the conductive substrate; then the cathode bottom active coating liquid obtained in step C is applied to the conductive substrate again, and the conductive substrate is heated to 420° C.-520° C. in an air atmosphere for 15 minutes-45 minutes, and this is repeated 6-12 times until the content of the oxide of the transition element group VIII in the metal oxide cathode bottom active coating is 6.7-15.3 g / m 2 ; In the step E, the conductive substrate is heated to 420° C.-520° C. in an air atmosphere for 15 minutes-45 minutes, thereby forming a metal oxide cathode active coating on the surface of the conductive substrate; then the cathode outer layer active coating liquid obtained in step C is coated on the conductive substrate again, and the conductive substrate is heated to 420° C.-520° C. in an air atmosphere for 15 minutes-45 minutes, and this is repeated 1-4 times until the ratio of the number of atoms of the transition element of group VIII in the metal oxide cathode outer layer active coating to the number of atoms of the transition element of group VIII in the metal oxide cathode bottom layer active coating reaches the requirement, that is, the ratio of the number of atoms of the transition element of group VIII in the metal oxide cathode bottom layer active coating to the number of atoms of the transition element of group VIII in the metal oxide cathode outer layer active coating is 5.9-23.4, thereby obtaining a high current density active gas precipitation cathode.
7. The method for preparing a high current density electrolytic active cathode according to claim 6, characterized in that: In the step C, based on the metal components, the ratio of the number of atoms of the transition elements of group VIII to the number of atoms of the lanthanide elements in the cathode bottom layer active coating liquid is 3.5-8.
9.
8. The method for preparing a high current density electrolytic active cathode according to claim 7, characterized in that: In the step C, based on the metal components, the ratio of the number of atoms of the transition elements of group VIII to the number of atoms of the lanthanide elements in the cathode bottom layer active coating liquid is 4.0-8.1.
Citation Information
Patent Citations
Activated cathode for hydrogen evolution
CN102762776A
Preparation method of sodium chlorate generator electrode
CN107034483A